2022
DOI: 10.36941/jesr-2022-0092
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Education and Mind-Body Disciplines: Exploring the Effects of the Pilates Method on Life Satisfaction, Mindfulness and Self-Compassion

Abstract: This study was aimed at exploring the potential of the Pilates Method of somatic education as a tool for enhancing factors influencing wellbeing. Specifically, the study focused on investigating whether Pilates Method mat-based and equipment practices affects mindfulness, self-compassion and life satisfaction among adults. A total of 129 adults (16 men and 113 women) participated in this study. Participants completed the Mindful Attention Awareness Scale, Self-Compassion Scale and Satisfaction with Life Scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…First, our results suggest that exercises that are part of Pilates programs are effective in activating the TrA during various movements. This is important because previous studies have shown that such exercises can improve core stability and function [ 12 ], reduce low back pain [ 41 ], and enhance quality of life [ 10 ] in different populations. Therefore, Pilates programs including such exercises may be beneficial for individuals who want to improve their core health and performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our results suggest that exercises that are part of Pilates programs are effective in activating the TrA during various movements. This is important because previous studies have shown that such exercises can improve core stability and function [ 12 ], reduce low back pain [ 41 ], and enhance quality of life [ 10 ] in different populations. Therefore, Pilates programs including such exercises may be beneficial for individuals who want to improve their core health and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Pilates is a popular exercise method developed by Joseph Pilates with its own philosophy and basic principles. The roots of Pilates come from ancient Greek and Eastern philosophy about mind body and spirit connection [ 10 , 11 ]. Today Pilates is divided into two types, the classic and the modern or contemporary, with many differences between them [ 11 ].…”
Section: Introductionmentioning
confidence: 99%